The Role of Digital Transformation and Perceived Organizational Support in Enhancing Financial Reporting Quality in Kurdistan’s Small and Medium Enterprises (SMEs): Digital Transformation and Perceived Organizational Support (Academic Journal of International University of Erbil, 2025)
Abstract This study explores the role of digital transformation (DT) and perceived organizational support (POS) in enhancing financial reporting quality (FRQ) in small and medium-sized enterprises (SMEs) in Kurdistan. Structural equation modelling was applied to primary data collected from 235 respondents including accountants, managers, owners, and other professional employees across three regions (Erbil, Sulaymaniyah and Dohuk). The analysis was conducted using Smart PLS 4 for structural equation modelling. The results show that DT has a notable and direct positive effect on FRQ, so confirming that using digital tools including ERP systems and cloud-based accounting software improves the accuracy, openness and timeliness of financial reports. Furthermore, the study shows that POS has a major impact on FRQ, meaning that workers who feel organizational support are more prone to participate in actions enhancing financial reporting. The mediation hypothesis was hence rejected since the mediation effect of POS between DT and FRQ was not supported. SMEs in Kurdistan should strike a mix between digital innovation and enough organizational support for sustainable development. Although bettering financial reporting depends on technological adoption, general organizational performance depends on employees feeling supported and valued.